Awareness Regarding Hypertension Among Hypertensive Patients Attending Hospital of Siddharthanagar Municipality - Neupane, Gita; Gyawali, Sanju; Sah, Chanda (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION Hypertension is one of the most common health condition that affects most of the population throughout the world and is a leading risk factor for morbidity and mortality. Hypertension related knowledge and practice such as life style modification, physical activity, nutrition etc. plays an important role in controlling and preventing its long-term complications of hypertension. The objective of the study was to find out the awareness of hypertension among hypertensive patients. MATERIAL AND METHODS A descriptive cross sectional study was conducted among 70 hypertensive patients selected as study sample by using non-probability purposive sampling technique. The data were collected by using semi-structured interview schedule and was analyzed by using descriptive and inferential statistics with Statistical Package for Social Sciences version 20. RESULTS The findings of the study revealed that more than half (52.9%) of respondents had low awareness regarding hypertension. CONCLUSION Based on the findings, it is concluded that more than half of the respondents have low awareness on hypertension. The respondents had low awareness on investigations of hypertension. Beside this, the respondents had high awareness regarding meaning, risk factors, main symptoms, causes, measures to control hypertension and complications of hypertension.